Program Matrikulasi Online untuk Meningkatkan Kesiapan Calon Kepala Sekolah - Ratna Juwita; Khamdani, Iqbal (Community: Jurnal Pengabdian Kepada Masyarakat, 2023)
This study aims: 1) to describe teacher’s learning readiness in principle preparation program; 2) to proof eligibility of Online Matriculation Program in Principal Preparation Training by expert judgement; 3) to proof effectiveness of Online Matriculation Program in order to improve teacher’s readiness in Principal Preparation Training. The method used in this study is research and development method. Dick, Carey, & Carey’s instructional design is used to develop the preliminary form. A total of 99 responses from teachers nominated as school principal who join the principal preparation training in Indonesia were analyzed by using the descriptive qualitative and quantitative model. Paired sample t-test and independent sample t-test are used to measure the effectiveness of the model The result of this study concludes that: 1) teacher’s readiness in Principal Preparation Program is low, 2) online matriculation program is eligible to use to improve readiness of teachers nominated as school principal, 3) online matriculation program positively influenced psychological and material readiness of teachers nominated as school principal. As paired-samples t-test proved that there is high level of statistical difference in point average received in learning readiness after online matriculatioan program  (p<0.005).